Assessing the levels of heavy metals Cd, Cr, and Pb in the naturally occurring red seaweed Gracilariopsis heteroclada in Iloilo Province, Philippines, for potential mass cultivation - RILEY A. BEUP; SAMANTHA GRACE E. FELONGCO; SHARMAINE JOY C. CAILIN; NICOLAS G. GUANZON JR.; RAYMUND N. FANTONALGO; ROLANDO V. PAKINGKING JR. (Smujo International, 2024)
Abstract. Beup RA, Felongco SGE, Cailin SJC, Guanzon Jr NG, Fantonalgo RN, Pakingking Jr RV. 2024. Assessing the levels of heavy metals Cd, Cr, and Pb in the naturally occurring red seaweed Gracilariopsis heteroclada in Iloilo Province, Philippines, for potential mass cultivation. Nusantara Bioscience 16: 149-153. The Philippines, a leading exporter of seaweed, has incorporated strategies in its Philippine Industry Seaweed Roadmap (2022-2026) to boost seaweed production. Therefore, to achieve this, potential sites for seaweed cultivation must undergo assessment for heavy metal content. A pilot study assessed heavy metals Cd, Cr, and Pb levels in red seaweed (Gracilariopsis heteroclada) sourced from three locations in Iloilo Province, Philippines: Site 1, a fishpond in Brgy, Nabitasan, Leganes; Site 2, along Dumangas Port coastline in Brgy, Sapao, Dumangas; and Site 3, a fishpond in Brgy, Talokgangan, Banate. Flame atomic absorption spectrometry was employed to analyze heavy metal concentrations. The mean concentrations of Pb in G. heteroclada from Sites 1, 2, and 3 were 5.0129±0.0896, 5.0388±0.8749, and 3.5119±0.9262 mg/kg, respectively; for Cr, they were 3.3002±0.1436, 4.0464±0.3800, and 2.8027±0.1436 mg/kg, respectively. The mean Cd concentrations were also 0.8518±0.0349, 0.8115±0.0202, and 0.5423±0.0419 mg/kg, respectively. Although Cd levels met safety standards, Pb and Cr concentrations exceeded the maximum permissible levels set by the European Union (EU) and China Food and Drug Administration (CFDA), respectively. This suggests that the examined sites may not be suitable for large-scale cultivation due to potential health risks from Pb and Cr exposure through seaweed consumption. Continued monitoring of toxic metal levels in these areas is therefore imperative.